2018
DOI: 10.1017/s147895151800024x
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of a group stress management Liver SMART intervention for patients with end-stage liver disease: A pilot study

Abstract: Twenty-nine English-speaking United Network for Organ Sharing-registered patients with end-stage liver disease from a single transplantation center enrolled in 8-week, group cognitive-behavioral liver stress management and relaxation training intervention adapted for patients with end-stage liver disease. Patients completed pre- and postintervention surveys that included the Beck Depression Inventory II and the Beck Anxiety Inventory. Feasibility, acceptability, tolerability, and preliminary efficacy were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Rationale: One study was identified that was specifically designed to assess the feasibility of delivering a psychosocial prehabilitation in solid organ transplant candidates. This study showed that a stress management and relaxation training program in liver transplant candidates was efficiently deliverable and considered acceptable and tolerable by the patients [67]. However, the enrolment rate was low, (29%) and the attrition rate was moderate (68%).…”
Section: Recommendation 41mentioning
confidence: 80%
See 3 more Smart Citations
“…Rationale: One study was identified that was specifically designed to assess the feasibility of delivering a psychosocial prehabilitation in solid organ transplant candidates. This study showed that a stress management and relaxation training program in liver transplant candidates was efficiently deliverable and considered acceptable and tolerable by the patients [67]. However, the enrolment rate was low, (29%) and the attrition rate was moderate (68%).…”
Section: Recommendation 41mentioning
confidence: 80%
“…[19][20][21][22][23][24][25], 7 for nutritional interventions [26][27][28][29][30][31][32], and 6 for psychosocial interventions [33][34][35][36][37][38]. In addition, 25 non-randomized studies regarding exercise , and 4 non-randomized studies on psychosocial interventions [65][66][67][68] were retrieved by literature review (Supplementary File S1). The small sample size per study and the limited size and heterogeneity of the total populations studied, the variability in interventions and outcomes measures, the generally low-to-moderate quality of the methodology, and-as a result-the inconsistency of findings across studies (Tables 2-4), warrants high-quality studies on multimodal prehabilitation before solid organ transplantation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When approaching retransplantation, patients often face a clinical deterioration that can be demoralizing. In this regard, it has been found that an 8-week cognitive behavioral stress management and relaxation training intervention is excellent for patients requiring solid organ transplantation [ 16 ]. Directing rehabilitative interventions towards goals that focus on maintaining function and avoiding physical deconditioning is of paramount importance in the preoperative period before LRT.…”
Section: Prehabilitation While Waiting For Lung Retransplantmentioning
confidence: 99%